2012
DOI: 10.5551/jat.10447
|View full text |Cite
|
Sign up to set email alerts
|

Management of Type IIb Dyslipidemia

Abstract: Although the Japan Atherosclerosis Society guideline for the diagnosis and prevention of atherosclerosis cardiovascular diseases for the Japanese population provides targets for low-density lipoprotein (LDL) cholesterol, triglycerides, and high-density lipoprotein (HDL) cholesterol to prevent cardiovascular disease in patients with dyslipidemia, there is no guideline specifically targeting the treatment of type b dyslipidemia, which is one of the most common types of dyslipidemia, along with type a and type dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
0
16
0
1
Order By: Relevance
“…The characteristics of the well recognized to be a cardiovascular risk factor [4][5][6][7] , and it is of health care importance to detect sustained hypertriglyceridemia as well as other metabolic abnormalities. Recently, the American Heart Association (AHA) scientific statement proposed 2.3 mmol/l (200 mg/dl) as a non-fasting cutoff point for screening 8) .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the well recognized to be a cardiovascular risk factor [4][5][6][7] , and it is of health care importance to detect sustained hypertriglyceridemia as well as other metabolic abnormalities. Recently, the American Heart Association (AHA) scientific statement proposed 2.3 mmol/l (200 mg/dl) as a non-fasting cutoff point for screening 8) .…”
Section: Resultsmentioning
confidence: 99%
“…Type IIb dyslipidemia is important, because it sometimes accompanies atherogenic lipid profiles, such as small dense LDL, remnant lipoprotein and low HDL cholesterolemia. It is also associated with type 2 diabetes mellitus, metabolic syndrome and chronic kidney disease (CKD), and most patients with familial combined hyperlipidemia (FCHL) show this phenotype . Therefore, it is necessary to understand that patients with type IIb dyslipidemia have a high risk for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Many lines of evidence show that low‐density lipoprotein cholesterol (LDL‐C) is an important risk factor for cardiovascular disease (CVD; CVD = IHD + CVA), but it is still debatable whether plasma triglyceride (TG) levels are associated with the occurrence of CVD. However, recent reports have shown that plasma TG levels are an independent risk factor for coronary artery disease (CAD) . In addition, non‐fasting TG levels have been shown to be associated with CAD and stroke .…”
Section: Introductionmentioning
confidence: 99%
“…визначено, що у хво-рих на ІХС та ЦД 2-го типу переважно спостері-гався IIb тип дисліпідемій, в осіб, які страждають на ІХС без ЦД, превалював IIа тип дисліпідемії [2]. Підтвердження переважання IIb типу дисліпі-демій у хворих на ІХС та ЦД 2-го типу знаходи-мо і в роботі японських учених на чолі з Arai H. та співавторів [8], де виявлено несприятливий вплив даного типу дисліпідемії на підвищення ризику розвитку серцево-судинних ускладнень у хворих на ЦД 2-го типу. Висновки 1.…”
Section: таблицяunclassified